Bright White Scattering from Protein Spheres in Color Changing, Flexible Cuttlefish Skin. (2nd April 2013) - Mäthger, Lydia M.; Senft, Stephen L.; Gao, Meng; Karaveli, Sinan; Bell, George R. R.; Zia, Rashid; Kuzirian, Alan M.; Dennis, Patrick B.; Crookes‐Goodson, Wendy J.; Naik, Rajesh R.; Kattawar, George W.; Hanlon, Roger T.
Abstract Throughout nature, elegant biophotonic structures have evolved into sophisticated arrangements of pigments and structural reflectors that manipulate light in the skin, cuticles, feathers and fur of animals. Not many spherical biophotonic structures are known and those described are often angle dependent or spectrally tuned. White light scattering by the flexible skin of cuttlefish (Sepia officinalis) is examined and how the unique structure and composition of leucophore cells serve as physiologically passive reflectors approximating the optical properties of a broadband Lambertian surface is investigated. Leucophores are cells that contain thousands of spherical microparticles called leucosomes that consist of sulfated glycoproteins or proteoglycans and reflectin. A leucophore containing ≈12 000 leucosome microspheres is characterized three‐dimensionally by electron microscopy and the average refractive index of individual leucosomes is measured by holographic microscopy to be 1.51 ± 0.02. Modeling of the ultrastructural data and spectral measurements with Lorenz‐Mie theory and Monte Carlo simulations suggest that leucophore whiteness is produced by incoherent scattering based upon a randomly ordered system. These soft, compliant, glycosylated proteinacious spheres may provide a template for bio‐inspired approaches to efficient light scattering in materials science and optical engineering.